Proizvodnja sekancev v Sloveniji - Jemec, Tina (Gozdarski vestnik, 2016)
Wood fuels market in Slovenia is very dynamic and fast developing. Slovenian forestry institute developed a methodology for monitoring a part of demand and supply of wood chips. Survey of wood chips production was conducted already three times. The last survey was finished in autumn 2015 and consists of data for 187 wood chippers. Data about wood chippers and their production in 2014 were collected by telephone survey. Based on all previous studies we can conclude that the number of wood chippers nearly doubled in the last few years (from 62 in 2008 up to 187 in 2015). According to collected data the total production of wood chips in 2014 amounted to over 1.500.000 loos m3.
Keywords: lesna goriva; lesni sekanci; sekalniki; obnovljivi viri energije; trg z energenti